(untitled) (Portuguese Journal of Family Medicine and General Practice, 2025)
Objectives: To perform the cultural adaptation of the Attitudes about Complex Therapy Scale (ACTS) to European spoken Portuguese as a scale of Atitudes Perante Terapêutica Complexa (APTC) and convergent validation with the Problems Areas in Diabetes-5 (PAID-5) scale. Methods: Translation into European Portuguese, linguistic verification, and back-translation into English, followed by an internal consistency analysis, comprehensibility, and reliability. Convergent validation was performed using the PAID-5 scale and context variables, including sex, age group, and Socio-Economic Deprivation Index (SEDI). Descriptive, factorial, and inferential statistical analyses were conducted. Results: In the cultural adaptation, involving 17 participants (52.9% female and 64.7% aged ≥64 years), there was no need for linguistic changes, nor was there a significant difference in test-retest reliability, p=0.066. In the validation study, involving 222 patients (53.6% male and 71.1% aged 65 or older), the APTC demonstrated good reliability (Cronbach’s α=0.743) and an intra-class correlation coefficient of 0.716, with four components accounting for 60.7% of the total variance. In the convergent validation, a moderate positive and significant correlation of APTC with PAID-5 was found (ρ=0.300, p<0.001), and a very weak and non-significant negative correlation (ρ=-0.113, p=0.092) between the APTC sum and the SEDI value. The APTC total did not vary significantly according to sex (p=0.377), family type (p=0.242), monthly income (p=0.064), and academic background (p=0.518). The APTC score (p=0.023) and the SEDI score (p=0.026) were significantly different according to age group, both with higher values in those ≤64 years. Discussion: The APTC encourages conversation between the general and family medicine doctors and the patient about the patient’s beliefs, attitudes, and difficulties regarding the management of multiple medications for a patient with multimorbidity, specifically diabetes. Conclusion: It was possible to adapt and validate the ACTS questionnaire for European Portuguese, the APTC, with good psychometric qualities.